Determinants of Vietnamese listed firm performance: Competition, wage, CEO, firm size, age, and international trade - Vu Thi Hanh; Nguyen Van Duy; Tung Manh Ho; Quan Hoang Vuong (Journal of Risk and Financial Management, 2019)
This study investigates the relationship between firms' competition, wage, CEOs' characteristics, and firm performance (measured by net income per employee, return on assets (ROA) and return on equity (ROE)) of Vietnam's 693 listed firms in 2015 using both the ordinary-least-square (OLS) and quantile regression methods. Triangulating the results coming from the analysis of three different measures of firm performance, this study consistently confirms that the sex of CEOs and chairman turns out to be insignificant in explaining firm performance and there is a negative association between capital intensity and firm performance. For financial firms, the age of a firm and average wage per employee are negatively associated with all types of firm performance. The quantile regression method shows that the age of a firm is negatively correlated with its net income per employee for small firms, while it is insignificant for medium-sized firms. Meanwhile, firm size is positively associated with firm performance. These results indicate Vietnam's business activities are still concentrating on low labor cost, labor intensive, and low-tech production, thus, policies that promote innovation and high-tech applications should be encouraged.
Keywords: 330; competition; wage; net income per employee; firm performance; productivity; Vietnam; listed company